1987
DOI: 10.1111/j.1432-1033.1987.tb10728.x
|View full text |Cite
|
Sign up to set email alerts
|

Urea synthesis from ammonia in periportal and pericentral regions of the liver lobule

Abstract: 1. Rates of urea synthesis were determined in periportal and pericentral regions of the liver lobule in perfused liver from fed, phenobarbital-treated rats by measuring the extra 0 2 consumed upon infusion of NH4C1 with miniature O2 electrodes and from decreases in NADPH fluorescence detected with micro-light-guides.2. Urea synthesis by the perfused rat liver supplemented with lactate (5 mM), ornithine ( 2 mM) and methionine sulfoximine (0.1 5 mM), an inhibitor of glutamine synthetase, was stimulated by stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…32 However, since urea is synthesized by liver, BUN will be lower than the normal level when the liver is severely damaged. 33 A low BUN/CRE ratio indicates reduction of BUN reabsorption caused by kidney damage. 31 In our study, Cd raised the serum CRE and BUN in the 0.2 and 1 mg/kg groups, indicating kidney filtration failure, but not in the 5 mg/kg group, which might have resulted from severe hepatomegaly and liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, since urea is synthesized by liver, BUN will be lower than the normal level when the liver is severely damaged. 33 A low BUN/CRE ratio indicates reduction of BUN reabsorption caused by kidney damage. 31 In our study, Cd raised the serum CRE and BUN in the 0.2 and 1 mg/kg groups, indicating kidney filtration failure, but not in the 5 mg/kg group, which might have resulted from severe hepatomegaly and liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques (for recent reviews see [5,9,10]) have been employed to study metabolic zonation in hepatic nitrogen metabolism: histochemistry [12], immunohistochemistry [13][14][15][16][17], in situ hybridization [18,19], retrograde/antegrade liver perfusion [20,21], microdissection [22], autoradiography (B. Stoll, H. P. Buscher & D. Haiussinger, unpublished work), radiolabelincorporation studies [23,24], studies on zonal cell damage [25,26], use of micro-lightguides and mini-oxygen electrodes [27], attempts to separate periportal from perivenous hepatocytes [28][29][30] and the dual-digitonin-pulse perfusion [31]. These studies revealed a remarkable development of functional hepatocyte heterogeneity with respect to ammonia and glutamine metabolism.…”
Section: Acinar Organization Of Nitrogen-metabolizing Pathwaysmentioning
confidence: 99%
“…On the basis of experiments with livers perfused with Krebs-Henseleit bicarbonate buffer in a non-recirculating system, Kari et al [6] proposed that urea synthesis is controlled by the oxygen tension and not by the concentration of ornithinecycle enzymes. In their experiments, flux through the ornithine cycle varied with the oxygen concentration, even though the concentration of oxygen (0.2-0.5 mM, which is non-physiologically high) was much higher than the value of 20 pM required for half-maximal oxygen uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained with suspensions of hepatocytes isolated from the portal and central areas have confirmed that the capacity of portal hepatocytes to synthesize urea is much higher than that of pericentral hepatocytes [5]. An opposing view is held by Kari et al [6]. According to these authors, oxygen tension is a major factor controlling urea synthesis in the intact liver.…”
mentioning
confidence: 99%
See 1 more Smart Citation